PEMAHAMAN, KEPUASAN PELANGGAN TERHADAP AKAD SALAM PADA TRANSAKSI JUAL BELI ONLINE - Dominggus, Sijauta; Muhammad, Yovi; Radhiyah, Radhiyah (Jurnal El Rayyan: Jurnal Perbankan Syariah, 2023)
Internet service users continue to increase every year, one of which is online buying and selling transactions. This is influenced by the increasing number of shopping sites that offer various conveniences. According to CNN Indonesia 2020 data, the shopping sites most visited by internet service users in 2019 were Tokopedia, Shoppee, Bukalapak, Lazada, Blibli, and others. In the Islamic perspective, online buying and selling transactions are related to the salam contract. Previous research analyzed the legal basis of the salam contract in online buying and selling transactions, but there is still little research on whether the customer has understood the basic nature of the salam contract. The purpose of this study is to analyze customer understanding and satisfaction with salam contracts in online buying and selling transactions. The research method used is a quantitative approach. The results of the study are expected to provide understanding and customer satisfaction with salam contracts in online buying and selling transactions.